The Notary's Responsibility for Unlawful Acts in Making Murabahah Contracts: Perspective of Islamic Law - Mustofa Abdul Basir; Neni Sri Imaniyati; Erny Kencanawati (Universitas Islam Malang, 2023)
This study aims to analyse the arrangements regarding the responsibility of notaries for unlawful acts in making contracts and analyse the implementation of notary responsibilities for unlawful acts in making murabahah contracts based on the perspective of Islamic law. This research uses a normative juridical approach method that is descriptive-analytical with literature data collection techniques and with legal interpretation analysis techniques. Based on the results of the study, it was obtained that based on the perspective of Islamic law, everyone will be held accountable for the actions they do through the process of qada'i or diyani and are prohibited from doing acts that cause harm both intentionally and unintentionally so that the form of notary responsibility can be personal responsibility, moral responsibility, social responsibility of society, and responsibility to God. The implementation of the responsibility of a Notary who is proven to have committed an unlawful act is the responsibility of the position (fautes de services) which is based on errors or omissions. Notaries, as defendants or co-defendants who are proven to have committed unlawful acts are decided to submit to the judge's decision and the murabahah contract made before the Notary and its derivative contracts, are declared void. Keywords: Responsibility, Notary, Unlawful Acts, Deeds, Islamic Law